Toothbrush, an Unusual Foreign Body - Bhattarai, A.; Adhikari, D.; Paudyal, N.; Giri, P.; Khadka, A.; Devkota, Y. (Kathmandu University Medical Journal, 2021)
Accidental consumption of foreign body is a common presenting complain among patients especially in young age group. Majority of patients can be discharged safely after reassurance while a fraction of patient requires observation and further management. Here we report a case of a 35-year-old gentleman who presented to the out-patient department of our hospital in June 2021 for accidental ingestion of toothbrush. After detailed history and physical examination upper gastrointestinal endoscopy was planned for the patient. Failed endoscopic removal was considered the indication for surgery. A supraumbilical midline incision was used to remove the toothbrush. Following the surgical removal, he was managed conservatively and was discharged without significant complications. We describe this case in detail in addition to reviewing the pertinent literature.